Investigation on end anchoring of CFRP strengthened steel I-beams - Narmashiri, K.; Jumaat, Mohd Zamin; Sulong, N.H.R. (Academic Journals, 2010)
Problems that frequently occur in carbon fibre reinforced polymer (CFRP) flexural strengthened steel structures include the peeling and debonding at the tip of the CFRP plate. This paper presents a study on the effectiveness of using steel plates and bolts as end-anchors to address these problems. Four steel I-beams were tested to failure. The first specimen was not strengthened and was used as the control beam. The second beam was strengthened with a CFRP plate without any end-anchoring. The third and fourth specimens were strengthened and end-anchored using steel plates and bolts. The number of bolts was the same, however, the length of the steel anchor plates was varied. The beams were tested under four point loads and loaded incrementally while the deflection and strain readings on the critical parts of the beams were recorded. For the numerical study, full three dimensional (3D) simulation and nonlinear static analysis was carried out using ANSYS software. The results indicate that the anchored beams had higher load capacities of up to 24 compared to the non-strengthened beam. End-anchoring with closer bolt spacing was more effective. Both experimental and numerical results are in good agreement highlighting the accuracy of the developed numerical model.